2012
DOI: 10.1108/15253831211286246
|View full text |Cite
|
Sign up to set email alerts
|

The international performance of standardizing and customizing Spanish firms

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 114 publications
(142 reference statements)
4
41
0
Order By: Relevance
“…This new thinking about how international activities are not globalized but regionalized (Rugman and Verbeke, 2004) has been confirmed, across various industries and time periods, by many papers (Beleska-Spasova and Glaister, 2009;Lee and Marvel, 2009;Rugman and Oh, 2010). Previously Rugman and Almodóvar (2011) and Almodóvar (2011Almodóvar ( , 2012 demonstrated that most international Spanish firms expand within their home region of the triad. It is difficult for them to transfer their business models to other regions out of the EU.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…This new thinking about how international activities are not globalized but regionalized (Rugman and Verbeke, 2004) has been confirmed, across various industries and time periods, by many papers (Beleska-Spasova and Glaister, 2009;Lee and Marvel, 2009;Rugman and Oh, 2010). Previously Rugman and Almodóvar (2011) and Almodóvar (2011Almodóvar ( , 2012 demonstrated that most international Spanish firms expand within their home region of the triad. It is difficult for them to transfer their business models to other regions out of the EU.…”
Section: Introductionmentioning
confidence: 88%
“…There are three main fits: a U-shaped relationship (Capar and Kotabe, 2003;Lu and Beamish, 2001;Ruigrok and Wagner, 2003); an inverted U-shaped relationship (Brock,Yaffe and Dembovsky, 2006;Gomes and Ramaswamy, 1999;Hitt, Hoskisson and Kim, 1997); and an S curve (Bae, Park and Wang 2008;Contractor, Kundu and Hsu, 2003;Lu and Beamish, 2004). There is also discussion of an inverted S curve (Chiang and Yu, 2005;Contractor, Kundu and Hsu, 2003;Ruigrok, Amann and Wagner, 2007), an M curve (Almodóvar, 2012;Lee, 2010) and an inverted M-curve relationship (Almodóvar, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The traditional argument to explain the formation of pyramidal structures is the separation of cash flow rights from control rights (Almeida & Wolfenzon, 2006). As cash flow rights as well as the control of the main owner are typically used in the definitions of Claessens et al (2002) and Faccio and Lang (2002), the first is measured by the sum of the products of the ownership proportion along the control chain, whereas the latter is measured as the minimal ownership proportion along the control chain.…”
Section: Pyramidal Ownershipmentioning
confidence: 99%
“…As cash flow rights as well as the control of the main owner are typically used in the definitions of Claessens et al (2002) and Faccio and Lang (2002), the first is measured by the sum of the products of the ownership proportion along the control chain, whereas the latter is measured as the minimal ownership proportion along the control chain. Thus, literature argues that it is common to adopt a pyramidal ownership structure when there is greater separation of control rights from cash flow rights (Almeida & Wolfenzon, 2006;Claessens et al, 2000), what is known as excess control rights.…”
Section: Pyramidal Ownershipmentioning
confidence: 99%
See 1 more Smart Citation